On a coupled system of functional integral equations of Urysohn type - Aziz, Nagat; Sayed, El; Mohamed, Sh (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper we shall study some existence theorems of solutions for a coupled system of functional integral equations of Urysohn type.